Planning a Safe EXIT: A Multidisciplinary Approach - Srijaya Reddy; Nina Deutsch (Association of American Medical Colleges, 2014)
Abstract This resource is a problem-based learning discussion case addressing the challenges and approaches to planning and safely executing an ex utero intrapartum treatment (EXIT) procedure. It is primarily aimed at pediatric anesthesiologists but also applies to health care providers in fetal medicine and surgery. The clinical scenario involves a fetus with a large cervical neck mass requiring an EXIT procedure for tracheal obstruction. This case highlights the challenges and implications of a procedure involving a multidisciplinary team. After presentation of the case stem, the instructor moderates a student-focused group discussion using a series of questions that build upon the case and the current literature. Evaluations of this problem-based learning discussion were uniformly positive.